Music-Dance (and Design) Relations in Ballet Productions of Ravel’s Daphnis et Chloé - Mawer, Deborah (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2012)
This article investigates music−dance (and design) interplay and balletic challenges in Daphnis et Chloé, focusing upon the Ravel−Ashton−Craxton production for The Royal Ballet (1951, revived in 2004), in comparison with the Ravel−Fokine−Bakst original of 1912. Sources drawn upon include accessible choreographic materials of Frederick Ashton (1904−88), held at the Royal Opera House Archives in London, as well as first-hand correspondence with the designer John Craxton (1922−2009). In order to explore the main music−dance relationships and emergent meanings, the study engages with multimedia ideas founded upon “consonance” and “dissonance” (Albright 2000), supported by music analytical (Cook 2001; 1998) and conceptual blending approaches (Fauconnier and Turner 2002). Particular moments from the ballet are selected for interpretation and, moving beyond rather over-simplified oppositions of unity versus independence or consonance versus dissonance, a case is made for complexes, transformation, and plurality.